Low temperature, pressureless sp2 to sp3 transformation of ultrathin, crystalline carbon films. (April 2019) - Piazza, Fabrice; Gough, Kathleen; Monthioux, Marc; Puech, Pascal; Gerber, Iann; Wiens, Richard; Paredes, Germercy; Ozoria, Cristhofer
Abstract: Nanosized and crystalline sp 3 -bonded carbon materials were prepared over large surface areas up to ∼33 × 51 μm 2 from the exposure of few-layer graphene (FLG) to H radicals produced by the hot-filament process at low temperature (below 325 °C) and pressure (50 Torr). Hybrid materials were also obtained from the partial conversion of FLG. sp 3 -C related peaks from diamond and/or lonsdaleite and/or hybrids of both were detected in UV and visible Raman spectra. CH bonding was directly detected by Fourier Transform Infrared (FTIR) microscopy over an area of ∼150 μm 2 and one single component attributed to sp 3 -CH mode was detected in the CH stretching band showing that carbon is bonded to one single hydrogen and strongly suggesting that the sp 3 -C materials obtained are ultrathin films with basal planes hydrogenated. The experimental results are compared to computational predictions and comprehensively discussed. Those materials constitute new synthetic carbon nanoforms after fullerenes, nanodiamonds, carbon nanotubes and graphene. This opens the door to new research in multiple areas for the development of new potential applications and may have wide scientific impact, including for the understanding of extraterrestrial diamond-related structures and polytype formation mechanism(s). Graphical abstract: Image 1